Interpretation of mercury content in national samples of sailfish (Istiophorus platypterus) and marlin (Makaira spp . Or Tetrapturus spp.) from international toxicological parameters - Calleja, Carlos E. (2014)
Total mercury results in eleven samples of sail fish and eleven samples of marlin from national market places (where they are called with those names), from a study by the Costarican Fishing Federation, are presented. Sail fish samples vary between 0,85 and 1,30 mg of mercury/kg of fish, with an average of (1,07±0,17) mg of mercury/kg of fish, and marlin samples varied between 0,41 and 1,18 mg of mercury/kg of fish with an average of (0,83±0,27) mg of mercury/kg of fish. Both cases showed mercury concentrations close to the maximum recommended value of the World Health Organization (WHO) of 1 mg of mercury/kg of fish for predatory species. At least 64% of the samples were equal to or above the toxicological threshold of WHO, defined as the provisional tolerable weekly intake, PTWI, calculated for portion sizes between 100 g and 150 g. Results show the presence of mercury in these samples, and are used to interpret mercury content compared to WHO values and propose recommendations for Costa Rica. These results are consistent with mercury accumulation in the ocean and in predatory fish observed worldwide, documented with a large number of references.